(untitled) (KULT_online, 2018)
The Atlas of the Irish Revolution, edited by John Crowley, Donal Ó Drisceoil, and Mike Murphy examines the revolutionary period in Ireland from 1912 to 1923, including the 19th century as the prelude to the revolution as well as its impacts, legacy, and memory. Comprised of over 100 contributions by numerous scholars and different perspectives, including maps and a striking visual dimension, the atlas represents one of the most comprehensive books about the revolutionary period in Ireland so far.